Youtube tutorial videos on developing math competencies in high school students: A theoretical review - Farfán-Pimentel, Johnny Félix; Sanabria-Rojas, Liz Gabriela; Terrones-Lavado, Emilia; Ricaldi-Ricaldi, Manuel Gilberto; Fuertes-Meza, Luis Carmelo; Tineo-Condeña, Marlon Yvan; Delgado-Vilca, José Martín (Seven Editora, 2023)
Education is one of the substantial factors for the development of a country, this will be achieved if the educational actors promote educational actions in order to raise the level of development of mathematical competences and consequently the improvement of the teaching-learning processes in the educational institutions; For this reason, from an innovative perspective, it is necessary to implement technological resources in the pedagogical work in order to strengthen the preparation of students; in this sense, technological tools such as YouTube video tutorials oriented to pedagogical practice require a reflective and coherent analysis that make it possible to enhance the mathematical competences of secondary education students. The research is a theoretical review of scientific literature, using the method of analysis and synthesis, exhaustive search of materials such as thesis reports, scientific articles, specialized literature, databases and information platforms related to the subject of study. The design was non-experimental, the documentary analysis technique was applied, resorting to information bases. The general objective was to analyze the strategy of YouTube video tutorials in the development of mathematical competences in high school students. DOI:https://doi.org/10.56238/innovhealthknow-051